Factors That Affect Work Stress, and Workload on Employee Performance - Rachel Yudia; Usfa Amelia Rahma (Yayasan Edukasi Cakrawala Nusantara, 2025)
Previous and related studies are very important for research and scientific articles. Previous or related studies strengthen theories and phenomena of relationships or influences between variables. In this work, factors that influence employee performance such as job stress and workload in the employee performance literature. The results of the research are significant and significant stress and burden on employee performance. Thus, the higher the stress and burden felt, the lower the employee's performance will be. This research can provide useful input to help companies take appropriate steps to improve employee performance by dealing with stress and problems that occur within the company.